Effects of a 12-week walking program on cardiovascular fitness and quality of life in breast cancer patients receiving adjuvant chemotherapy. - Vexler, Liisa. (University of Ottawa (Canada), 1999)
Background. Previous studies have shown that aerobic activity such as a walking program help to maintain cardiovascular fitness, body composition, and QOL in breast cancer patients undergoing adjuvant therapy. Methods. Twenty women with histologically proven stage I--II breast cancer were randomized into either an experimental or control group. The patients began the program the same week that they began their chemotherapy treatments. Ten patients participated in a supervised walking program at the Ottawa Regional Cancer Centre which consisted of walking around a track for a minimum of twenty minutes three times per week, and on their own at home a minimum of two times per week, while ten patients served as served as a control group. Cardiovascular fitness, body composition, and quality of life (QOL) were compared at the time of entry into the study and 12 weeks later. Findings. The results of the present study suggest that a 12-week walking program, in this sample of stage I--II breast cancer patients undergoing adjuvant chemotherapy, does not affect QOL or body composition. Only one measure of cardiovascular fitness was affected. The findings may have been more significant if not for the fact that 50% of the usual care group became physically active.
Keywords: Health Sciences, Rehabilitation and Therapy.